The Framing of Sustainable Consumption and Production in SDG 12. (28th January 2019) - Gasper, Des; Shah, Amod; Tankha, Sunil
Abstract: This paper examines the processes of formulation of UN Sustainable Development Goal 12 (SDG 12) – 'Ensure Sustainable Consumption and Production Patterns' – and its targets and indicators. We argue that business interests have steered its narrative of sustainable growth. The outcome of the SDG 12 negotiations reflects a production‐ and design‐centered perspective that emerged in the 1990s and has a business‐friendly regulatory approach and faith in solutions through new technologies. We show how the targets and indicators emerged in debates between national governments, UN agencies, civil society and private sector organizations – and how they reflect both the political process and technical and practical considerations in translation of a broad concept into the SDG format. While the emergence of SDG 12 as a standalone goal stems from a push by developing countries to build pressure on developed countries, and its presence may open space for attention to this area in the future, many of its targets were watered down and left vague. The indicators to measure progress on the targets further narrow the scope and ambition of Goal 12, whose current content does not adequately reflect earlier more transformative conceptualizations of Sustainable Consumption and Production. Abstract : Most of the targets under SDG 12 do not yet have satisfactory indicators. Enunciation of the targets may yet spur further work and real actions.